THE EFFECT OF SELECTION EMPLOYEERS AND CONTROL WORK AGAINTS THE PERFORMANCE EMPLOYEES IN BANK BTN PEKANBARU - Rezki Pratiwi; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The Purpose of this research to find out how about the effect of selection employeers and scrutiny work againts the performnanceemployees in bank btn Pekanbaru . Selection as an independent variable (X1) consist of , education selection, work experience, healty., personal And control as independet variale (X2) consist of, determinaton of standart of work,the result of the work measurement,correction. And than performance as independen variable(Y) as work quality, personall quality, quantity, timeliness, independence.The research used sample of the employee of Bank BTN Pekanbaru. The number of this sample is 57 persons with slovin. This research is also used propertionate sratified random sampling. Data of this research is primary data, with spread questions to the nurses. The data analysis of this research is statistical analysis with SPSS program.This research shows that selection emplooyee as independent variable is positive implications for the employee in Bank BTN Pekanbaru as coefficeents determination value (R2) is 74,4 it mens that 74,4% and 25,6% is not served in this researvh.Keyword : Selection, Controling, Performance. Bank